EGFR-selective activation of CD27 co-stimulatory signaling by a bispecific antibody enhances anti-tumor activity of T cells - Melo, Vinicio; Nelemans, Levi Collin; Vlaming, Martijn; Lourens, Harm Jan; Wiersma, Valerie R.; Bilemjian, Vrouyr; Huls, Gerwin; de Bruyn, Marco; Bremer, Edwin (Frontiers in Immunology, 2023)
A higher density of tumor infiltrating lymphocytes (TILs) in the tumor microenvironment, particularly cytotoxic CD8+ T cells, is associated with improved clinical outcome in various cancers. However, local inhibitory factors can suppress T cell activity and hinder anti-tumor immunity. Notably, TILs from various cancer types express the co-stimulatory Tumor Necrosis Factor receptor CD27, making it a potential target for co-stimulation and re-activation of tumor-infiltrated and tumor-reactive T cells. Anti-cancer therapeutics based on exploiting CD27-mediated T cell co-stimulation have proven safe, but clinical responses remain limited. This is likely because current monoclonal antibodies fail to effectively activate CD27 signaling, as this receptor requires higher-order receptor cross-linking. Here, we report on a bispecific antibody, CD27xEGFR, that targets both CD27 and the tumor antigen, epidermal growth factor receptor (EGFR). By targeting EGFR, which is commonly expressed on carcinomas, CD27xEGFR induced cancer cell-localized crosslinking and activation of CD27. The design of CD27xEGFR includes an Fc-silent domain, which is designed to minimize potential toxicity by reducing Fc gamma receptor-mediated binding and activation of immune cells. CD27xEGFR bound to both of its targets simultaneously and triggered EGFR-restricted co-stimulation of T cells as measured by T cell proliferation, T cell activation markers, cytotoxicity and IFN-γ release. Further, CD27xEGFR augmented T cell cytotoxicity in a panel of artificial antigen-presenting carcinoma cell line models, leading to Effector-to-Target ratio-dependent elimination of cancer cells. Taken together, we present the in vitro characterization of a novel bispecific antibody that re-activates T cell immunity in EGFR-expressing cancers through targeted co-stimulation of CD27.